Development of Wordwall-Based Gamification on Question Exercises about French Cross-Cultural - Polili, Andi Wete; Ghofur, Abdul (Budapest International Research and Critics University, 2022)
This study aims to produce the development of Wordwall-based gamification media supported by Cross-cultural. The method used in this study is the Research and Development method with five phases of the ADDIE model according to Branch (2009), namely (1) Analysis (2) Design (3) Development (4) Implementation (5) Evaluation. The application of wordwall-based gamification development was carried out as many as 4 materials that had an average pre-test score of 60.5% with a grade of